Debate as A Learning-Teaching Method: A Survey of Literature - Arskal Salim (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
Abstract This present paper explored historical references of debate trend to be proposed as one of learning-teaching method. By analyzing the strengths and limitations of debate, the author found that any existing debate format is imperfect and it is educators’ task to seek out how in utilizing debate as a learning teaching method. Some works on debate assessment method were described. In real implementation, on author's experience to use debate as learning-teaching method, showed that it was difficult to mark students either as individual or team. Therefore, their preparation and the performance in-class debate should be considered. Abstrak Artikel ini mengeksplorasi referensi sejarah dari tren debat yang akan diusulkan sebagai salah satu metode belajar mengajar. Dengan menganalisis kekuatan dan keterbatasan perdebatan, penulis menemukan bahwa format debat yang ada tidak sempurna dan itu adalah tugas pendidik untuk mencari tahu bagaimana memanfaatkan debat sebagai metode pengajaran pembelajaran. Beberapa karya pada metode penilaian debat dijelaskan. Dalam implementasi nyata, pengalaman penulis menggunakan debat sebagai metode belajar-mengajar, menunjukkan bahwa hal itu sulit untuk menandai siswa baik sebagai individu atau tim. Oleh karena itu, persiapan mereka dan perdebatan kinerja dalam kelas harus dipertimbangkan. How to Cite: Salim, A. (2015). Debate as A Learning-Teaching Method: A Survey of Literature. TARBIYA: Journal of Education In Muslim Society, 2(1), 97-104. doi:10.15408/tjems.v2i1.1665. Permalink/DOI:http://dx.doi.org/10.15408/tjems.v2i1.1665